Oral manifestations of gastroesophageal reflux disease in children: A preliminary observational study - Kothimbakkam Sai Sarath Kumar; Jayanthi Mungara; Nilaya Reddy Venumbaka; Poornima Vijayakumar; Deebiga Karunakaran (Wolters Kluwer Medknow Publications, 2018)
Aims: This study aimed to document the prevalence of oral manifestations seen among pediatric gastroesophageal reflux disease (GERD) patients in Chennai, Tamil Nadu, India. Methodology: This study was performed at various children's hospitals in Chennai. Fifty-one GERD patients who were assessed by endoscopy and 24 h pH-metry, 31 (60.78%) males and 20 (39.21%) females, aged 2-12 years (mean age, 7.43 years), comprised the study group. All patients answered a detailed frequency questionnaire related to regurgitation and acidic foods and participated in a clinical dental examination. Statistical Analysis Used: Data were analyzed using the SPSS statistical software package version 19. Results: Among the GERD patients, 42 (82.35%) had dental erosion. A total of 668 (57.98%) deciduous teeth and 484 (42.02%) permanent teeth were examined, of which dental erosion was detected in 248 (21.52%) and 171 (14.84%) teeth, respectively. The most commonly affected primary tooth was the occlusal surface of the maxillary posteriors and commonly affected permanent tooth was occlusal surface of the mandibular molars. Conclusions: There may be a positive correlation between GERD and dental erosion. According to this study, presence of erosion, especially in posterior teeth, could be a key to diagnose GERD and refer the child to the gastroenterologist.